A risk‐based forecast of extreme mortality events in small cetaceans: Using stranding data to inform conservation practice. Issue 4 (27th February 2019) - Bouchard, Colin; Bracken, Cameron; Dabin, Willy; Van Canneyt, Olivier; Ridoux, Vincent; Spitz, Jérôme; Authier, Matthieu
Abstract: Effective conservation requires monitoring and pro‐active risk assessments. We studied the effects of at‐sea mortality events (ASMEs) in marine mammals over two decades (1990–2012) and built a risk‐based indicator for the European Union's Marine Strategy Framework Directive. Strandings of harbor porpoises ( Phocoena phocoena ), short‐beaked common dolphins ( Delphinus delphis ), and striped dolphins ( Stenella coeruleoalba ) along French coastlines were analyzed using Extreme Value Theory (EVT). EVT operationalizes what is an extreme ASME, and allows the probabilistic forecasting of the expected maximum number of dead animals assuming constant pressures. For the period 2013–2018, we forecast the strandings of 80 harbor porpoises, 860 common dolphins, and 57 striped dolphins in extreme ASMEs. Comparison of these forecasts with observed strandings informs whether pressures are increasing, decreasing, or stable. Applying probabilistic methods to stranding data facilitates the building of risk‐based indicators, required under the Marine Strategy Framework Directive, to monitor the effect of pressures on marine mammals.